1996
DOI: 10.1104/pp.112.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Insect Control and Dosage Effects in Transgenic Canola Containing a Synthetic Bacillus thuringiensis cryIAc Gene

Abstract: The seeds of a number of Brassica L. species are cultivated for the production of oil. Collectively, the oilseed Brassica sp., generally referred to as rapeseed, supply more than 13% of the world's supply of edible oils and rank third behind soybean and oil palm in importance. The term "canola" was adopted by the Canadians in 1979 and used to describe oilseed Brassica cultivars that produce oils containing less than 2% erucic acid and to describe defatted seed meals with less than 30 pmol g-' of aliphatic gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 21 publications
7
78
0
3
Order By: Relevance
“…The reasons for the decreased expression are not clear. Using the same construct we (Stewart et al, 1996) have produced transgenic canola with expression levels of up 0.4%, and Singset et al (1996) have produced transgenic peanut with expression levels of 0.18%. It is generally accepted that, when producing severa1 independently transformed plants, expression levels are greatly variable.…”
Section: Transgene Lntegration and Expressionmentioning
confidence: 99%
“…The reasons for the decreased expression are not clear. Using the same construct we (Stewart et al, 1996) have produced transgenic canola with expression levels of up 0.4%, and Singset et al (1996) have produced transgenic peanut with expression levels of 0.18%. It is generally accepted that, when producing severa1 independently transformed plants, expression levels are greatly variable.…”
Section: Transgene Lntegration and Expressionmentioning
confidence: 99%
“…Although no commercial lines of Bt-producing Brassica napus L. have been released, experimental transgenic Bt-producing B. napus lines have been generated that confer selective advantage in the presence of Brassica-defoliating insects, including diamond back moth (Plutella xylostella L.), cabbage looper (Trichoplusia ni Hübner) and corn earworm [Helicoverpa zea (Boddie)] (Halfhill et al, 2001;Stewart et al, 1996Stewart et al, , 1997Ramachandran et al, 1998a). A number of transgenic Bt-producing Brassica vegetable crops are also being developed, including broccoli (B. oleracea L. var.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicated that transgene location in the genome and accumulation of transgenes may affect fitness in volunteer populations of B. napus. In the United States, Stewart et al (1996) produced a series of transgenic B. napus lines containing the insecticidal Bt transgene and evaluated these in the laboratory and the field (Stewart et al 1997). Under insect selection pressure in the field, transgenic plants had increased fitness due to reduced defoliation compared with their non-transgenic counterparts when allowed to naturalize following cultivation.…”
Section: Herbicide Resistancementioning
confidence: 99%